Cytotoxic and genotoxic effects of Kalanchoe pinnata (Lam.) Pers. fresh leaf juice in the cultured human blood lymphocytes. (2nd January 2022) - Bhavsar, Shruti; Chandel, Divya
Abstract: This is the first investigation on the in vitro cytotoxicological and genotoxicological effects of Kalanchoe pinnata (Lam.) Pers. fresh leaf juice, for establishing a safe and effective quantity for use. Peripheral blood of 6 healthy, non-addicted males between 20 and 25 years of age was used for toxicity assessment by 3-(4, 5-dimethylthazol-2-yl)-2, 5-diphenyl tetrazolium bromide (MTT), mitotic index (MI), sister chromatid exchanges (SCEs) and Cytokinesis Blocked Micronucleus (CBMN) assays. The IC50 of the leaf juice calculated by MTT assay was 155.1 µl. The 50 and70 µl of the juice concentrations were decided after standardization by MI and showed non-significant and significant decrease respectively when compared to control. The SCEs/Cell and SCEs/Chromosome were increased non-significantly (50 µl) and significantly (70 µl), while cell cycle proliferative index, Average generation time and Population doubling time values were non-significant for both doses when compared to the controls. In CBMN assay, the Cytokinesis block proliferation index, cytotoxicity, Micronuclei, Nuclear bud, Nucleoplasmic bridge frequencies and total DNA damage biomarkers showed non-significant changes for both 50 and 70 µl. The changes observed were significant only at 70 µl for MI and SCEs, which were significantly lower than that by positive control indicating a non genotoxic effect. Hence, the fresh leaf juice can be used pharmaceutically as well as traditionally, but for long durations and higher doses should be used with caution, as it can have mutagenic effect at particularly high levels.